INTERNAL CSR AND ISLAMIC BANKING PERFORMANCE - Nur Faliza (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Internal CSR is an important part of corporate social responsibility. Although the survey results reveal that businesses with CSR practices are able to increase employee interest in the company and potential employees so that the benefits of CSR can be felt by businesses, CSR practices for employees are still neglected. This study aims to examine the effect of internal CSR on organizational commitment and the effect of organizational commitment on performance. This study was conducted on permanent employees of Aceh Islamic Banks, which amounts to 325 sample and the sampling technique used simple random sampling. Using a questionnaire as a research instrument with a self-administered method. PLS-SEM is a data analysis method used in this study with the Smartpls 3 analysis tool. The study found that internal CSR that is empowerment, skill development and work environment affect on organizational commitment but skill development has no significant effect on organizational commitment. Furthermore, organizational commitment have a significant effect on maqasid al sharia and job performance at Islamic banking in Aceh.